2013
DOI: 10.4049/jimmunol.1300436
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Clearance of Neutrophil Extracellular Traps Is a Silent Process

Abstract: Neutrophil extracellular traps (NETs) facilitate the extracellular killing of pathogens. However, in recent years, excessive NET formation has been implicated in several pathological conditions. Indeed, NETs that are not removed from tissues or from the circulation might serve to trigger autoimmune responses. We observed that physiological amounts of DNase I do not suffice to completely degrade NETs in vitro, suggesting that additional mechanisms are required for the removal of these extracellular structures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
292
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 341 publications
(329 citation statements)
references
References 43 publications
16
292
1
4
Order By: Relevance
“…Also, in our experiments, we observed that IgA-induced NETs were able to ensnare live bacteria, but bacterial viability was not diminished (data not shown). As such, it is possible that, in addition to direct cytotoxic effects, NETs also function to contain bacteria for removal by other immune cells like macrophage (42,43). In fact, dying of PMNs through NETosis may have a second function besides the release of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in our experiments, we observed that IgA-induced NETs were able to ensnare live bacteria, but bacterial viability was not diminished (data not shown). As such, it is possible that, in addition to direct cytotoxic effects, NETs also function to contain bacteria for removal by other immune cells like macrophage (42,43). In fact, dying of PMNs through NETosis may have a second function besides the release of NETs.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, PMN can control DC activation via several mechanisms [reviewed in (26,27)]. The effects of NETs on APC maturation are unclear (21,(42)(43)(44). We thus took advantage of our previously described method for preparing and quantifying isolated functional NETs (5) to study the impact of calibrated NETs on moDC maturation and its functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…These reports tend to support a proinflammatory effect of NETs on APCs. However, an in vitro study showed no proinflammatory effect of NETs alone on macrophages (44), and aggregated NETs promote the resolution of inflammation in a murine gout model (45). The conflicting effects reported in the literature might be related to technical variations in NET preparation and APC models.…”
mentioning
confidence: 99%
“…La rupture conjointe des membranes nucléaire et granulaire conduit au mélange des composants cytoplasmiques, granulaires et nucléaires, puis la rupture de la membrane plasmique permet la libération des NET dans l'espace extracellulaire (Figure 2). Afin de maintenir l'homéostasie, les NET sont ensuite dégradés par l'action conjointe de la DNase 1 et d'un mécanisme d'endocytose impliquant les macrophages [4]. En parallèle de ce modèle « classique », plusieurs études ont rapporté un phénomène de nétose rapide (5-60 min) dans différents modèles expérimentaux [5][6][7].…”
unclassified